Lower Carboniferous calcareous algae and foraminifera of the middle part of the central paraxial zone of the Dono-Dnieper Depression (Ukraine) - Gusarova, Anastasiia; Matveyev, Andrij (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2021)
Introduction. Today, the boundary of the Upper Visean and Lower Visean substage of the Dnieper-Donetsk Basin (DDB) remains controversial. The characteristic of associations of foraminifera and calcareous algae of Lower Carboniferous deposits in axial zone of the DDB were investigated. Analysis of previous publications. The Tournaisian-Visean stage is most studied in the riparian zones of the DDB, and the axial zone is much less studied. This is due to the deep occurrence of Visean rocks in this area, as well as, sometimes, the lack of Tournaisian deposits in a particular section. Materials and methods. The microfacies of carbonate rocks on the core materials of the borehole 203 Berezivs`ka. The algoflora fossil associations characterizes the algae zone Palaeoberesella lahuseni – Exvotarisella index – Nanopora woodi, which was compared with foraminifera zones Uralodiscus rotundus and Paraarchaediscus koktjubensis. Results and discussion. Lithology. The upper part of the section is dominated by pack-, grаn-packstones, which indicates the normal conditions of sedimentation and the development of depleted marine fauna. From the middle part of the section there are light layers of bioclastic waxstones, which indicates limited water circulation. In the lower part there is a high percentage of bioorganic detritus. Green algae and foraminifera paraturaminides play a significant role in the number of individuals. Micropaleontology. Describes the association of foraminifera, represented by individuals of 24 genera, the association of algae, represented by 35 species belonging to 25 genera, including 3 species of calcareous algae, which are described for the first time for DDB: Atractyliopsis cf. cumberlandensis, Nanopora undata and Exvotarisella maponi. Conclusions. A comparative analysis of the algae associations described in the paper with the coeval associations of the Urals, East European Platform (Russian Platform), Belgium, France and Lviv-Volyn basin. The foraminifera and algae representation is given at the 8 paleontological plates. As a result of stratigraphical and lithological studies, the following conclusions can be drawn. The section of Berezivska well is represented mainly by carbonate, as well as sand and clay rocks of the lower part of the Upper Visean substage (Tulian horizon) and the upper part of the Lower Visean substage (Bobrikovskian horizon). Microfacial analysis revealed a number of rocks in Visean The upper part of the section is dominated by pack-, grаn-packstones, which indicates the normal conditions of sedimentation and the development of depleted marine fauna. From the middle part of the section there are light layers of bioclastic waxstones, which indicates limited water circulation. In the lower part there is a high percentage of bioorganic detritus. Green algae and foraminifera paraturaminides play a significant role in the number of individuals. These deposits accumulated in the conditions of an open carbonate platform with normal sea conditions. Even lower there are large forms of red algae. The rocks turn into algae packstone and wak- packstone. Bioclastic material are represented by a few foraminiferal shells, fragments of exotarizel and a large number of various, partially rolled, biodetrite. These deposits accumulated in conditions close to the edge of the platform Describes the association of foraminifera, represented by individuals of 24 genera, the association of algae, represented by 35 species belonging to 25 genera, including 3 species of calcareous algae, which are described for the first time for DDB: Atractyliopsis cumberlandensis, Nanopora undata and Exvotarisella maponi. The large number of archedicides from the core №4 indicates that the bottom substrate was represented by soft silt, and their developed radiant layer indicates the most favourable conditions for their development. In the upper part of the section in the association of calcareous algae the number of individuals is dominated by green siphonocladian algae, which indicates a calm hydrodynamic regime below the tidal level, as well as the optimal depth of the basin, which does not exceed 3-5 m. Microfauna and algae of Late Visean, in comparison with the Early Visean, becomes taxonomically impoverished. Numerous archaedicides appear in the Late Visean carbonate deposits. Attention should be paid to Paraarchaediscus koktjubensis as a zonal form of the Tulian horizon. The Early Visean Association of calcareous algae of the axial zone of the DDD differs markedly from the single age association of the open Donbass by the absence of taxonomically diverse paleoberezelides, as well as a large number of large thallites of red algae.